The Effect of Family Literacy Program Towards Improving of Parental Involvement in Early Childhood Education - Salman Hasibuan; Hayuni Husni; Lokot Daulay (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
The aims of the research are: 1) to raise parents’s awareness and improve their participation at school and home; 2) to empower children’s character; 3) to develop children’s academic attainements. The research used correlational method. The samples of the reseach are parents from private early childhood education school of Darul Ilmi Murni Deli Serdang. The findings: 1. Family literacy programs applied by parents are effectively increased parental involvement neither at schools nor at home; 2. The Correlation Coefficient value is known to be 0.913 greater than r (table) 0.349 meaning that there is a significant correlation between the family literacy program and improvement family involvement at school. The Family Literacy Program and the Improvement of Family Involvement at school are classified as near perfect because they are in the> 0.91 range.